Critiquing Print Media Transformation and Black Empowerment in South Africa: A Critical Race Theory Approach. Issue 4 (3rd July 2020) - Govenden, Prinola; Chiumbu, Sarah
ABSTRACT: South Africa is a country found on extreme forms of inequality along race, gender, and class lines. Thus, transformation addressing these inequalities of the apartheid past became a critical factor in the re-organisation of society at the onset of democracy in 1994. One essential intervention in addressing mainly the economic disparities of the past was Black Economic Empowerment (BEE), introduced by the African National Congress (ANC) government to overcome the economic legacy of apartheid. The BEE programme, renamed the Broad-Based Black Economic Empowerment (B-BBEE) in 2007, measures the transformation performance of companies across all sectors of the economy, according to a specified scorecard. In the absence of a media-specific transformation policy, the Act serves as its transformation policy standard. This paper critiques the B-BBEE policy instrument in relation to print media transformation using Critical race theory, and related concepts, such as racial capitalism, and racial liberalism. The paper finds that despite the racial diversification of the racial composition of the media, B-BBEE is largely an illusion. The B-BBEE strategy has not changed the racial character of the economy, and fundamentally resulted in the co-optation of a small black elite into the wealthy white capitalist elite inherited from the apartheid era, where the "power relationship" reminiscent of apartheid still exists and white privilege intersects with other forms of subordination such as gender and class. Policies supporting media transformation must become "race conscious" in a way that openly confronts racism and engages with systematic racism and exclusion.